Association between grandparent coresidence and weight change among first‐grade Japanese children. Issue 8 (29th March 2019) - Morita, Ayako; Ochi, Manami; Isumi, Aya; Fujiwara, Takeo
Summary: Background: The prevalence of grandparent coresidence is increasing. However, the impact of grandparent coresidence on weight change among school‐age children remains unclear. Objectives: The objective of the study is to examine the association between grandparent coresidence and obesity‐related behaviours and change in body mass index (BMI) z scores among school‐age children. Methods: In total, 3422 caregivers of first‐grade children in Adachi City, Tokyo, participated in surveys and health checkups in 2016 and 2017 with no change in their grandparent coresidence status (response rate: 80.1% and 81.4%, respectively). Association between grandparent coresidence and obesogenic dietary, physical activity, and screen‐based sedentary behaviours was measured using Poisson regression with robust error variance analysis, while change in BMI z scores was determined by linear regression and adjusting for potential covariates. Results: Grandparent coresidence was associated with increased prevalence rate (PR) of irregular snack foods intake (PR: 1.38, 95% confidential interval (CI): 1.19, 1.61); however, children who live with grandparents showed a lower BMI z scores in the second grade (coefficient: −0.048, 95% CI: −0.094 to −0.0013) after adjustment for BMI z scores in the first grade, family sociodemographics, and obesogenic behaviours. Conclusion: Grandparent coresidence is associated with lower BMI z scores among early primary school‐age Japanese children living in urban areas.